Pengaruh Dimensi Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Good Deal Restaurant - Primananda, Putu Bayu Dewangga; Setiawan, Putu Yudi (E-Jurnal Manajemen, 2014)
Perception of service quality is reflected in consumers assessment of the realities and expectations of the service he felt. Tangibles, reliability, assurance, responsiveness, and empathy are the five dimensions of service quality. Some 126 respondents were selected as the study sample. Multiple linear regression analysis techniques as data analysis techniques used in testing the impact of service quality on customer satisfaction on Good Deal Restaurant. Results of testing of physical evidence, reliability, assurance, responsiveness, and empathy as a dimension of service quality on customer satisfaction in a Good Deal Restaurant showed a significant positive effect. The results of this test indicate that consumer satisfaction visited Good Deal Restaurant is affected by the quality of service offered. Key words : tangibles, reliability, responsiveness, assurance, emphaty